Financial Performance and Audit Committee Characteristics: An Empirical Study on Bahrain Services Sector - OUDAT, MOHAMMAD SALEM; ALI, BASEL J. A.; QESHTA, MOHAMMED HELMI (The journal of contemporary issues in business and government, 2021)
Purpose: The main purpose of this research paper is to investigate the association of audit committee characteristics and financial performance among services sector corporation-listed in Bahrain Stock Exchange. Design/methodology/approach: In this research paper, the corporations listed on the Bahrain Stock Exchange for the period from 2012 to 2019 are examined. To fulfill the current purpose of the research paper, the linear panel regression method is employed. However, the audit committee characteristics represented by expertise, board independence, board size and frequently meetings are the independent variables of the current study, and return on equity and earning per share a proxy of financial performance are the dependent variables. Corporation’s size, leverage and age are examined as control variables. Findings: There is significant relationship between ACID, ACMEET, FSIZE and the performance (ROA, ROE and EPS). there is no statistical significance between the ACFE, ACS, FAGE and performance (ROA, ROE and EPS), the LVRGE have an impact on EPS but not on ROA, ROE. Practical implications: The findings of the current research paper expected to be important for government and corporations policymakers in constructing an appropriate set of governance mechanisms related to the audit committee characteristics, and for current and potential investors in shaping their understanding of corporate governance code and it’s principles in Bahrain context.